Aperture-adjustable porous radiation refrigeration material and preparation method thereof

Through the combination of cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene) composite materials and nano alumina, a porous radiation refrigeration material with adjustable pore size is prepared, which solves the high cost, complex process and The problem of poor thermal and humidity comfort has achieved efficient radiation refrigeration effect and is suitable for a variety of application scenarios.

CN119264525APending Publication Date: 2025-01-07DONGHUA UNIV

Patent Information

Application Number
CN202411241193.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing radiation refrigeration materials have problems such as high cost, complex process, poor flexibility, easy cracking or low production efficiency, and it is difficult to maintain thermal and humidity comfort in high temperature environments.

Method used

Using cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene) composite materials, a porous structure with adjustable pore size is prepared by solvent-nonsolvent-induced phase separation method, and nano-alumina is introduced to form an efficient porous radiation refrigeration material. , suitable for films, fabrics and other surfaces.

Benefits of technology

It achieves high solar reflectivity and high infrared emissivity, reduces temperature and is low in cost, is suitable for high-temperature environments, the material is soft and moisture-permeable, and is suitable for cooling of human bodies and buildings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264525A_ABST
    Figure CN119264525A_ABST
Patent Text Reader

Abstract

The invention relates to an aperture-adjustable porous radiation refrigeration material and a preparation method thereof. The aperture-adjustable porous radiation refrigeration material is prepared by introducing inorganic nanoparticles onto a polymer-based composite material, wherein the polymer matrix composite material is prepared by compounding cellulose acetate and poly (vinylidene fluoride-co-hexafluoropropylene); the material is endowed with a layered porous structure through a solvent-nonsolvent induced phase separation method, and materials with different pore sizes are prepared by adjusting the proportion of a mixed solvent. By adjusting the proportion of the mixed solvent, the size and morphology of the pores can be adjusted, so that the reflectivity of the material to sunlight is enhanced, and the preparation method has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new materials, and particularly relates to a porous radiation refrigeration material with adjustable pore size and a preparation method thereof. Background Art

[0002] Thermal comfort is essential for humans to maintain normal physiological functions and daily activities. High temperature environment will affect people's work efficiency and even cause health problems such as heat stroke, dehydration, and heat exhaustion. At present, active cooling is usually used to improve heat stress, such as air conditioning and fan cooling, but traditional cooling methods consume a lot of energy. The energy consumed by air conditioning in summer accounts for more than 15% of global electricity consumption, exacerbating the greenhouse effect and bringing a heavy burden to the economy and the environment. Therefore, there is an urgent need for a clean and environmentally friendly cooling method to achieve thermal management while reducing energy consumption and provide humans with a comfortable living and production environment.

[0003] Passive radiative cooling can reduce the temperature of an object by reflecting the radiation of sunlight (wavelength 0.25-2.5 μm) and effectively radiate heat to outer space through the atmospheric long-wave infrared transparent window (wavelength 8-13 μm) without the need for external energy. Therefore, radiative cooling is considered to be one of the cutting-edge and potential technologies to alleviate energy and environmental pressures.

[0004] Among the current public technologies regarding radiation refrigeration materials, patent CN 108995257B discloses a radiation refrigeration film and a preparation method thereof, including a base film, a reflective layer and a hardened layer, wherein the hardened layer includes an upper hardened layer and a lower hardened layer. The material is multi-layered and thick, which affects its wearability, and the reflective layer is made of metal materials such as gold, silver, aluminum, and chromium, which has a high cost. Patent CN 117567878A discloses a high-performance porous radiation refrigeration filler and a preparation method thereof, using titanium oxide as a raw material and preparing it into a material with an amorphous structure to avoid the influence of different crystal forms on the radiation refrigeration performance. Graphite oxide is used as a pore-forming template material, mixed with it and subjected to high-temperature treatment, while burning the graphite oxide, the pore structure left behind is maintained to the greatest extent, and finally a radiation refrigeration material with a porous structure is obtained, but its process is precise, the preparation method is complex, and it exists in the form of a filler, which needs to be sprayed or added to other materials for use. CN 117304769A discloses a refrigeration coating and a preparation method thereof, comprising: a reflective layer, an interface layer, a radiation layer, and a protective layer arranged in sequence from bottom to top, wherein the thickness of the reflective layer is 50-200 μm, the thickness of the interface layer is 20-50 μm, the thickness of the radiation layer is 120-400 μm, and the thickness of the protective layer is 50-100 μm. The thickness is relatively thick, the coating has poor flexibility, is relatively brittle and is prone to cracking. Patent CN 114481636B discloses a textile coating with a radiation refrigeration function and a preparation method thereof. The textile coating is prepared by coating a coating with a radiation refrigeration function, comprising a water-based acrylic resin, a reflective pigment filler, a dispersant, a wetting agent, a defoaming agent, a thickener, a film-forming aid and water. The textile coating forms a functional layer on the surface of the textile material by a one-step coating method. The reflectivity of the functional layer in visible light and infrared light is ≥85%, and the emissivity in the 7μm-14μm band is ≥85%. The coating composition is complex and the optical performance is average. Patent CN113818123B discloses a method for preparing a radiation cooling functional fabric, which comprises mixing and dissolving two or more polymers with different solubility, heating and stirring until the solution has viscosity to obtain a slurry, and then using wet spinning to make the slurry into yarn, and the obtained yarn is passed through a coagulation bath and then dried to make a fabric to obtain the radiation cooling functional fabric. The invention improves the reflectivity of sunlight by forming a porous structure, and by wet spinning two or more polymers, it ensures both the strength of the yarn and a certain elasticity, but the invention still does not solve the problem of the fabric sticking to the skin and causing a stuffy feeling after a large amount of sweating.Patent CN 116790087A discloses a dual-selective radiation cooling material and a method for making the same. The radiation cooling material includes polyoxymethylene and polytetrafluoroethylene, and is characterized in that it can selectively emit infrared rays in both the first atmospheric window band (8μm to 13μm) and the second atmospheric window band (16μm to 25μm), that is, it has high selective thermal emissivity in both atmospheric window bands, and is a dual-selective thermal emitter. However, the invention uses electrospinning to prepare the radiation cooling material, which has low production efficiency and high requirements for spinning conditions. Professor Cui Yi of Stanford University and others reported a nano-PE material (Radiative human body cooling by nanoporouspolyethylene textile [J]. Science, 2016, 353: 1019-1023) in Science, which can be used as an infrared radiation heat dissipation fabric material for cooling the human body in summer. Polydopamine is coated on the surface of nanoPE, which is modified to be hydrophilic, enhancing moisture absorption and perspiration and air permeability. However, commercial polyethylene has poor heat resistance, with a maximum operating temperature of around 80°C. The material is prone to deformation when heated, affecting its use. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a porous radiation refrigeration material with adjustable pore size and a preparation method thereof. The material has excellent optical properties and can not only be directly made into a film, but also can be used on various surfaces such as fabrics, wood, and metal using traditional spraying and dipping processes.

[0006] The present invention provides a porous radiation refrigeration material with adjustable pore size, wherein the material is obtained by introducing inorganic nanoparticles into a polymer-based composite material; wherein the polymer-based composite material is composited by cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene); the material is given a layered porous structure by a solvent-non-solvent induced phase separation method, and materials with different pore sizes are prepared by adjusting the ratio of a mixed solvent.

[0007] Preferably, the inorganic nanoparticles are nano-alumina.

[0008] Preferably, the nano-alumina is in α phase and has a particle size of 30-100 nm.

[0009] The present invention provides a method for preparing a porous radiation refrigeration material with adjustable pore size, comprising the following steps:

[0010] (1) adding inorganic nanoparticles into a mixed solvent of a first solvent and a second solvent, magnetically stirring at room temperature, and ultrasonically dispersing to obtain a uniform solution;

[0011] (2) adding cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene) to the uniform solution obtained in step (1), heating and stirring at 55-65° C. for 2-4 hours to obtain a mixed solution;

[0012] (3) allowing the mixed solution obtained in step (2) to stand at room temperature to eliminate bubbles;

[0013] (4) applying the solution after standing in step (3) on the surface of a clean substrate, and immersing the substrate in a water tank after standing. After the immersion is completed, taking out the film and placing it in a vacuum oven or freeze-drying it to obtain a porous radiation refrigeration material.

[0014] Preferably, the mass ratio of the first solvent to the second solvent in step (1) is 9:1 to 3:7.

[0015] Preferably, the first solvent in step (1) is N-methylpyrrolidone; and the second solvent is acetone.

[0016] Preferably, the magnetic stirring time in step (1) is 10-15 min; and the ultrasonic dispersion time is 30-40 min.

[0017] Preferably, the mass ratio of cellulose acetate to poly(vinylidene fluoride-co-hexafluoropropylene) in step (2) is 7:1 to 1:7.

[0018] Preferably, the mass of the inorganic nanoparticles is 0.1% to 12% of the total mass of cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene).

[0019] Preferably, the standing time in step (3) is 6-12 hours.

[0020] Preferably, the soaking time in step (4) is 15-45 minutes.

[0021] Preferably, the porous radiation refrigeration material obtained in step (4) is in the form of a film with a thickness of 200-300 μm.

[0022] The present invention uses cellulose acetate and poly (vinylidene fluoride-co-hexafluoropropylene) to achieve a high solar reflectivity (93.4%) in the 0.25-2.5 μm solar radiation band and a high infrared emissivity (98.6%) in the 8-13 μm atmospheric window band. The introduction of cellulose acetate and the presence of a porous structure improve the hydrophilicity of the film, making the film soft and breathable, and improving the thermal comfort when used in a hot and humid environment. According to Mie scattering, when the pore size is close to the wavelength, scattering will occur. Although common electrospinning technology can also give the material a nanoporous structure, the spinning conditions of electrospinning are relatively harsh, the production cost is high, and the thickness is not easy to adjust. The present invention imparts a layered porous structure through a solvent-nonsolvent induced phase separation method, and prepares materials with different pore sizes by adjusting the ratio of the mixed solvent. The method is simple, controllable, and easy to implement. The regulated material has 250-800nm ​​nanopores, which can scatter visible light with a wavelength equivalent to the pore size. When light propagates in the micropores of 1 to 2.3μm inside the material, it can increase its reflective ability through multiple diffuse reflections, further enhancing the optical properties of the material.

[0023] Beneficial Effects

[0024] (1) The present invention utilizes the high solar reflectivity and high infrared emissivity of cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene), and introduces inorganic nanoparticles to enhance Mie scattering, to prepare a porous radiation refrigeration material with excellent optical properties. The prepared material has a high solar reflectivity in the 0.25μm-2.5μm solar radiation band, reducing the temperature rise caused by sunlight; it has a high infrared emissivity in the 2.5μm-14μm mid-infrared band, allowing heat to be released into the universe through the atmospheric window; and it has good thermal stability, with no weight loss at room temperature to 100°C, making it suitable for cooling in high temperature weather environments. (2) The preparation method of the present invention is simple, does not require additional metal substrates such as gold and silver to increase the reflectivity, and has low cost.

[0025] (3) The material prepared by the present invention is in the form of a liquid and can be directly coated, sprayed, or impregnated on other glass, wood boards, or textile fabrics. It can be widely used for cooling objects, human bodies, and buildings.

[0026] (4) The present invention can control the absorption, reflection and scattering of the film to a specific wavelength band by optimizing parameters such as solvent ratio, solute ratio, nanoparticle addition amount and film thickness. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The reflectance spectra of the films in Examples 1-4 were measured using a UV-visible-near infrared spectrophotometer equipped with a barium sulfate integrating sphere.

[0028] Figure 2 The infrared emission spectra of the films in Examples 1-4 were measured using a Fourier transform infrared spectrometer equipped with a gold integrating sphere. Figure 3 (a) The surface scanning electron microscope image of the film of Example 1; (b) The surface scanning electron microscope image of the film of Example 2; (c) The surface scanning electron microscope image of the film of Example 3; (d) The surface scanning electron microscope image of the film of Example 4.

[0029] Figure 4 This is the TG curve of the film of Example 2 at a heating rate of 10°C / min.

[0030] Figure 5 The reflectance spectra of the films in Examples 5-9 were measured using a UV-Vis-NIR spectrophotometer equipped with a barium sulfate integrating sphere.

[0031] Figure 6 The infrared emission spectra of the films in Examples 5-9 were measured using a Fourier transform infrared spectrometer equipped with a gold integrating sphere.

[0032] Figure 7 ATR-FTIR spectra of the films of Examples 5-9.

[0033] Figure 8 is the water contact angle of the film of Examples 5-9.

[0034] Fig. 9 This is a surface scanning electron microscope image of Example 7.

[0035] Fig.10 The reflectance spectra of the films in Comparative Example 1, Example 6, and Examples 10-12 were measured using a UV-Vis-NIR spectrophotometer equipped with a barium sulfate integrating sphere.

[0036] Fig.11 The infrared emission spectra of the thin films in Comparative Example 1, Example 6, and Examples 10-12 were measured using a Fourier transform infrared spectrometer equipped with a gold integrating sphere.

[0037] Fig.12 This is a temperature change diagram of the film of Example 6 used in an indoor simulated solar radiation test.

[0038] Fig.13 This is an infrared thermal imaging image of the film of Example 6 used in an indoor simulated solar radiation test.

[0039] Fig.14 This is a real-time temperature change diagram of the lower surface covered with the film of Example 6 and the pure cotton fabric in an outdoor environment.

[0040] Fig.15 This is a diagram showing the cooling effect of covering the film of Example 6 and pure cotton fabric in an outdoor environment. DETAILED DESCRIPTION

[0041] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0042] Example 1

[0043] Add 0.16g of nano-alumina to a mixed solvent of 4.5g of N-methylpyrrolidone and 0.5g of acetone, stir magnetically at room temperature for 10min, and disperse ultrasonically for 30min to obtain a uniform solution. Add 0.75g of cellulose acetate and 0.75g of poly(vinylidene fluoride-co-hexafluoropropylene) to the uniform solution, heat and stir at 65°C for 2h to fully dissolve and mix the materials to obtain a mixed solution, and let it stand at room temperature for 6h to eliminate bubbles. Apply the defoamed solution on the surface of the cleaned substrate, let it stand for 10min, then immerse the substrate in a water tank for 45min. After immersion, take out the film and freeze-dry it for 24h to obtain a porous radiation refrigeration film.

[0044] Example 2

[0045] The masses of N-methylpyrrolidone and acetone were changed to 3.5 g and 1.5 g respectively to obtain the corresponding porous radiative cooling film. The other conditions were the same as those in Example 1.

[0046] Example 3

[0047] The masses of N-methylpyrrolidone and acetone were changed to 2.5 g and 2.5 g respectively to obtain the corresponding porous radiative cooling film. The other conditions were the same as those in Example 1.

[0048] Example 4

[0049] The masses of N-methylpyrrolidone and acetone were changed to 1.5 g and 3.5 g respectively to obtain the corresponding porous radiative cooling film. The other conditions were the same as those in Example 1.

[0050] Figure 1 and Figure 2The solar reflectance spectra and infrared emissivity spectra of the films in Examples 1-4 are shown. When the mass ratio of NMP to acetone is 9:1, 7:3, 1:1 and 3:7, the average reflectance in the 0.25-2.5 μm band is 99.3%, 101.1%, 94.4% and 89.9%, respectively; the average emissivity in the 2.5-14 μm band is 89.1%, 88.5%, 88.2% and 94.1%, respectively. With the reduction of NMP and the increase of acetone, the solubility of the polymer in the mixed solvent decreases, affecting the uniformity of the solution, and further affecting the film forming properties and optical properties.

[0051] Figure 3 The SEM images of the films in Examples 1-4 are shown in Figure 1-4. When the acetone content in the mixed solvent is less than 50%, the good solvent NMP is dominant, the polymer is fully dissolved in the mixed solution, the polymer chain is relatively stretched and not easily entangled, the membrane surface layer is mainly composed of polymer network pores and polymer micelle aggregate pores, the average pore size is small, and the structure is relatively uniform. Figure 3 a, When the mass ratio of NMP to acetone in the mixed solvent is 9:1, the film is composed of nanopores of 75 nm. Increasing the content of acetone increases the pore size of the film and a hierarchical porous structure appears, such as Figure 3 As shown in Figure b, this is due to the existence of the "slow phase separation" phenomenon. When the coated nascent film and the substrate are immersed in a water bath together, the acetone in the nascent film flows into the water bath, resulting in an increase in the polymer concentration in the top layer, where nucleation occurs. After a certain period of time, the surface layer enters the phase separation region, and new holes gradually grow near the surface layer. When the mass ratio of NMP to acetone in the mixed solvent is 7:3, the pores in the film are mainly nanopores of 250 to 800 nm and micropores of 1 to 2.3 μm. This pore size can effectively reflect sunlight and improve the optical properties of the porous film. When the acetone content in the mixed solvent is not less than 50%, the surface of the film is mainly liquid-liquid phase separation pores, with a large average pore size and an uneven structure. With the increase of acetone, the nascent film will undergo phase separation in a very short time after being immersed in a water bath, that is, "instantaneous phase separation", resulting in the formation of large holes, making the porous film have a low reflectivity in the visible light region.

[0052] Figure 4 The thermogravimetric curve of Example 2 shows that the film has no mass loss when heated to 100° C., indicating that the material is suitable for cooling in hot weather.

[0053] Example 5

[0054] Add 0.16g of nano-alumina to a mixed solvent of 5.6g of N-methylpyrrolidone and 2.4g of acetone, stir magnetically at room temperature for 10min, and disperse ultrasonically for 30min to obtain a uniform solution. Add 1.75g ​​of cellulose acetate and 0.25g of poly(vinylidene fluoride-co-hexafluoropropylene) to the uniform solution, heat and stir at 65°C for 2h to fully dissolve and mix the materials to obtain a mixed solution, and let it stand at room temperature for 6h to eliminate bubbles. Apply the defoamed solution on the surface of the cleaned substrate, let it stand for 10min, then immerse the substrate in a water tank for 30min. After immersion, take out the film and freeze-dry it for 24h to obtain a porous radiation refrigeration film.

[0055] Example 6

[0056] The masses of cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene) were changed to 1.5 g and 0.5 g respectively to obtain the corresponding porous radiative cooling film. The other conditions were consistent with those in Example 5.

[0057] Example 7

[0058] The masses of cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene) were changed to 1.0 g and 1.0 g respectively to obtain the corresponding porous radiative cooling film. The other conditions were consistent with those in Example 5.

[0059] Example 8

[0060] The masses of cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene) were changed to 0.5 g and 1.5 g respectively to obtain the corresponding porous radiative cooling film. The other conditions were consistent with those in Example 5.

[0061] Example 9

[0062] The masses of cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene) were changed to 1.75 g and 0.25 g, respectively, to obtain the corresponding porous radiative cooling film. The other conditions were consistent with those in Example 5.

[0063] Figure 5 and Figure 6 The solar reflectance spectra and infrared emissivity spectra of the films in Examples 5-9. When the mass ratio of cellulose acetate to PVDF-HFP is 7:1, 3:1, 1:1, 1:3 and 1:7, the average reflectance in the 0.25-2.5 μm band is 89.9%, 93.4%, 98.5%, 101.6% and 90.1% respectively; the average emissivity in the 2.5-14 μm band is 93.9%, 93.0%, 88.5%, 79.5% and 93.0% respectively. According to Figure 7It can be seen from the infrared spectra of Examples 5-9 that after reducing the amount of cellulose acetate, the strong infrared emission performance of the C=O functional group in the atmospheric transparent window weakened, and with the increase of PVDF-HFP, the stretching vibration absorption peak of CF2 and the deformation vibration absorption peak of CH2 connected to CF2 began to increase.

[0064] Figure 8 is the water contact angle of the film of Example 5-9. It can be seen from the figure that the hydrophilicity of the film is not simply related to the content of hydrophilic cellulose acetate. When the content of poly(vinylidene fluoride-co-hexafluoropropylene) is low, as the content of cellulose acetate decreases, the pore density and porosity of the porous radiative cooling film gradually increase, and the surface hydrophilicity is better. Fig. 9 The SEM image of Example 7 shows that the membrane surface has no skin layer and has high porosity. When the cellulose acetate content continues to decrease, the hydrophobicity of the fluorine-containing PVDF-HFP polymer gradually becomes stronger than the synergistic effect of cellulose acetate and the porous structure.

[0065] Comparative Example 1

[0066] 1.5g of cellulose acetate and 0.5g of poly(vinylidene fluoride-co-hexafluoropropylene) were added to a mixed solvent of 5.6g of N-methylpyrrolidone and 2.4g of acetone, and heated and stirred at 65°C for 2h to fully dissolve and mix the materials to obtain a mixed solution, which was allowed to stand at room temperature for 6h to eliminate bubbles. The defoamed solution was applied to the surface of the cleaned substrate, and after standing for 10min, the substrate was immersed in a water tank for 30min. After the immersion, the film was taken out and freeze-dried for 24h to obtain a porous radiative cooling film.

[0067] Example 10

[0068] Add 0.12g of nano-alumina to a mixed solvent of 5.6g of N-methylpyrrolidone and 2.4g of acetone, stir magnetically at room temperature for 10min, and disperse ultrasonically for 30min to obtain a uniform solution. Add 1.5g of cellulose acetate and 0.5g of poly(vinylidene fluoride-co-hexafluoropropylene) to the uniform solution, heat and stir at 65°C for 2h to fully dissolve and mix the materials to obtain a mixed solution, and let it stand at room temperature for 6h to eliminate bubbles. Apply the defoamed solution on the surface of the cleaned substrate, let it stand for 10min, then immerse the substrate in a water tank for 30min. After immersion, take out the film and freeze-dry it for 24h to obtain a porous radiation refrigeration film.

[0069] Embodiment 11

[0070] The mass of nano-alumina was changed to 0.2 g to obtain the corresponding porous radiation refrigeration film. The other conditions were consistent with those in Example 10.

[0071] Example 12

[0072] The mass of nano-alumina was changed to 0.24 g to obtain the corresponding porous radiation refrigeration film. The other conditions were consistent with those in Example 10.

[0073] Fig.10 and Fig.11 The solar reflectivity spectra and infrared emissivity spectra of the films in Comparative Example 1, Example 6, and Examples 10-12 are shown. When the mass of nano-alumina is 0%, 8%, 6%, 10% and 12% of the total mass of cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene), the average reflectivity in the 0.25-2.5 μm band is 87.7%, 93.4%, 89.3%, 91.5% and 91.2% respectively; the average emissivity in the 2.5-14 μm band is 91.7%, 93.0%, 93.0%, 91.7% and 91.6% respectively. The addition of reflective inorganic particles can improve the solar reflectivity in the ultraviolet-visible-near infrared region, but if the content is too high, it will cause agglomeration and sedimentation at the bottom of the solution, affecting the performance.

[0074] A film with an area of ​​1×2 cm was prepared according to Example 6. A pure cotton fabric of the same size and thickness was cut as a comparison sample.

[0075] The cooling performance of the sample under simulated solar radiation was investigated in the laboratory. The xenon lamp was placed 20 cm away from the sample and maintained at 1 sun irradiance (1000 W / m 2 ), the samples and the control samples were placed on insulating polystyrene foam to reduce the heat transfer and heat radiation from the environment. The test time was 60 minutes for a heating and cooling cycle. K-type thermocouples were used to monitor and record the temperature under the sample and control sample in real time. Infrared thermal imaging technology was used to monitor the temperature changes on the material surface.

[0076] Depend on Fig.12 and Fig.13 It can be seen that under 1 sun irradiance, the temperature of the porous radiation cooling film and the pure cotton fabric will rise, and reach a thermal equilibrium state in 10 minutes. At this time, the air temperature covered by the pure cotton fabric is about 39°C, and the air temperature covered by the porous radiation cooling film is about 32°C, which can maintain the temperature within the thermal comfort range of the human body, and can achieve a maximum cooling of 7.7°C. This shows that the radiation cooling film has a good cooling effect. A circular film with a diameter of 9 is prepared according to Example 6. Pure cotton fabric of the same size and thickness is cut as a comparison sample.

[0077] The radiation cooling performance of the sample was tested by building a device. Four 12x12x5cm cavities were made on the surface of a 30x30x30cm polystyrene foam box. The thermocouple was placed in the center of the cavity and fixed to test the temperature of the lower surface of the sample. The sample was tightly covered on the thermocouple. At the same time, a cavity was reserved to place only the thermocouple probe without covering the sample to test the ambient temperature. The surface of the foam box except the cavity was wrapped with aluminum foil to reduce the heating of the test device by sunlight. The top of the device was covered with infrared transparent polyethylene film to isolate the heat convection and heat conduction from the surrounding environment.

[0078] like Fig.14 and Fig.15 As shown, when the solar intensity reaches 975.2W / cm 2 In the outdoor environment, the temperature of the cotton fabric rises quickly and the heat is easily accumulated. The porous radiation cooling film has a significant cooling effect, with the maximum cooling range reaching 13.4℃.

Claims

1. A porous radiation cooling material with adjustable pore size, characterized in that: The material is obtained by introducing inorganic nanoparticles into a polymer-based composite material; wherein the polymer-based composite material is composited by cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene); the material is given a layered porous structure by a solvent-nonsolvent induced phase separation method, and materials with different pore sizes are prepared by adjusting the ratio of the mixed solvent.

2. The porous radiation cooling material with adjustable pore size according to claim 1, characterized in that: The inorganic nanoparticles are nano-alumina.

3. The porous radiation cooling material with adjustable pore size according to claim 2, characterized in that: The nano-alumina is in α phase and has a particle size of 30-100 nm.

4. A method for preparing a porous radiation cooling material with adjustable pore size, comprising the following steps: (1) adding inorganic nanoparticles into a mixed solvent of a first solvent and a second solvent, magnetically stirring at room temperature, and ultrasonically dispersing to obtain a uniform solution; (2) adding cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene) to the uniform solution obtained in step (1), heating and stirring at 55-65° C. for 2-4 hours to obtain a mixed solution; (3) allowing the mixed solution obtained in step (2) to stand at room temperature to eliminate bubbles; (4) applying the solution after standing in step (3) on the surface of a clean substrate, and immersing the substrate in a water tank after standing. After the immersion is completed, taking out the film and placing it in a vacuum oven or freeze-drying it to obtain a porous radiation refrigeration material.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the first solvent to the second solvent in the step (1) is 9:1 to 3:

7.

6. The preparation method according to claim 4 or 5, characterized in that: The first solvent in step (1) is N-methylpyrrolidone; the second solvent is acetone.

7. The preparation method according to claim 4, characterized in that: The mass ratio of cellulose acetate to poly(vinylidene fluoride-co-hexafluoropropylene) in the step (2) is 7:1 to 1:

7.

8. The preparation method according to claim 4, characterized in that: The mass of the inorganic nanoparticles is 0.1% to 12% of the total mass of cellulose acetate and poly(vinylidene fluoride-co-hexafluoropropylene).

9. The preparation method according to claim 4, characterized in that: The standing time in step (3) is 6-12 hours.

10. The preparation method according to claim 4, characterized in that: The soaking time in step (4) is 15-45 minutes.

Citation Information

Patent Citations

  • A radiation cooling film and a preparation method thereof

    CN108995257B

  • A method for preparing a radiation-cooling functional fabric

    CN113818123B

  • A textile coating with radiation cooling function and its preparation method

    CN114481636B

  • Double-selective radiation refrigeration material and manufacturing method thereof

    CN116790087A

  • Refrigeration coating and preparation method thereof

    CN117304769A

Cited By

  • Radiation refrigeration functionalized polyethylene non-woven fabric and preparation method thereof

    CN120006536A